The lived experience of adults with cystic fibrosis: what they would tell their younger selves about the gut. Issue 2 (25th November 2019) - Cave, L.; Milnes, L. J.
Abstract: Background: Little is known about adults' experience of living with cystic fibrosis (CF) specifically in relation to the gut. However, their unique perspectives may be meaningful to children with CF and inform the understanding and practice of dietitians. The present study aimed to explore adults' lived experience of the CF gut and how they learnt to manage the gut as they were growing up. Methods: Semi‐structured interviews were conducted with adult inpatients ( n  = 10). Interviews were audio‐recorded, transcribed verbatim and accounts analysed using interpretative phenomenological analysis. Results: Three super‐ordinate themes were identified: taking Creon, the learning process and this much I (now) know . Participants accounts of how CF affects the gut predominantly focused on taking Creon (pancreatin, Mylan). Various strategies were employed for coping with peer responses to taking Creon at school. Several participants reached adulthood before they understood and/or accepted that taking Creon consistently needed to be normal for them. Knowledge and understanding developed over time, with 'CF experience' and was shaped by family, CF care teams and other children with CF. All had unmet information needs when growing up. Having key explanations earlier, to make connections between eating, taking Creon, gaining weight and growth, did or would have helped most participants. Participants urged children to be assertive, ask questions and not only be involved in managing their diet and gut, but also begin to take control of this aspect of their CF. Conclusions: Supporting development of knowledge, skills and confidence to manage diet and the gut needs to be integral to care throughout childhood.